Addressing the Common Pathway Underlying Hypertension and Diabetes in People Who Are Obese by Maximizing Health: The Ultimate Knowledge Translation Gap. (13th February 2011) - Dean, Elizabeth; Lomi, Constantina; Bruno, Selma; Awad, Hamzeh; O'Donoghue, Grainne
Abstract : In accordance with the WHO definition of health, this article examines the alarming discord between the epidemiology of hypertension, type 2 diabetes mellitus (T2DM), and obesity and the low profile of noninvasive (nondrug) compared with invasive (drug) interventions with respect to their prevention, reversal and management. Herein lies the ultimate knowledge translation gap and challenge in 21st century health care. Although lifestyle modification has long appeared in guidelines for medically managing these conditions, this evidence-based strategy is seldom implemented as rigorously as drug prescription. Biomedicine focuses largely on reducing signs and symptoms; the effects of the problem rather than the problem. This article highlights the evidence-based rationale supporting prioritizing the underlying causes and contributing factors for hypertension and T2DM, and, in turn, obesity. We argue that a primary focus on maximizing health could eliminate all three conditions, at best, or, at worst, minimize their severity, complications, and medication needs. To enable such knowledge translation and maximizing health outcome, the health care community needs to practice as an integrated team, and address barriers to effecting maximal health in all patients. Addressing the ultimate knowledge translation gap, by aligning the health care paradigm to 21st century needs, would constitute a major advance.